2012
DOI: 10.1111/j.1748-5967.2012.00468.x
|View full text |Cite
|
Sign up to set email alerts
|

Lamellicorn beetles (Coleoptera: Scarabaeoidea) in Korea and Mongolia

Abstract: This work was undertaken as an initial part of the collaborative effort between Korean and Mongolian researchers to study the terrestrial and aquatic insects in these countries. An analysis of data on faunal composition, taxonomic diversity and biogeographical structure of lamellicorn beetles in Korea and Mongolia was conducted in order to characterize the faunal relations between two countries. The Korean fauna of lamellicorn beetles is almost two fold greater in both generic diversity and species richness th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…The flower chafer Osmoderma opicum (Coleoptera: Scarabaeidae) is distributed throughout Korea and Japan (Won et al 1998;Bayartogtokh et al 2012). In Korea, it is found yearly in the north-eastern mountainous areas, from July to August, but with rarity, and thus, is listed as a class II endangered wild animal in Korea (Won et al 1998).…”
mentioning
confidence: 99%
“…The flower chafer Osmoderma opicum (Coleoptera: Scarabaeidae) is distributed throughout Korea and Japan (Won et al 1998;Bayartogtokh et al 2012). In Korea, it is found yearly in the north-eastern mountainous areas, from July to August, but with rarity, and thus, is listed as a class II endangered wild animal in Korea (Won et al 1998).…”
mentioning
confidence: 99%
“…Similar to other telecoprid species, Gymnopleurus mopsus (Scarabaeidae), is also under threat of local extinction throughout its distribution in Palearctic regions, including in Asia 11 and Europe 6 , 8 . Previous studies have reported that both G .…”
Section: Introductionmentioning
confidence: 99%
“…Because Mongolia is the only region where large G . mopsus populations are currently maintained in the north-eastern Palearctic region 11 , it has the value as the species’ last “refuge” and, as such, is considered important for future conservation and restoration efforts. However, the present-day population genetic structure shaped by contemporary processes (e.g., ongoing gene flow among populations in relation to anthropogenic habitat fragmentation and distributional changes) as well as demographic (population) history (e.g., dispersal, isolation, population contraction/expansion and bottleneck) of G .…”
Section: Introductionmentioning
confidence: 99%
“…The ability of the dung beetles to utilize large herbivore dung as a food source and nest chamber is the key innovation to their evolutionary success, along with the development of numerous morphological and behavioral adaptations, such as the rolling of dung (Villalba et al ). However, their population size and distributional range have rapidly decreased worldwide, especially in the Palaearctic region (Simmons & Ridsdill‐Smith ; Bayartogtokh et al ).…”
Section: Introductionmentioning
confidence: 99%
“…The dung beetle species, Gymnopleurus mopsus Pallas, 1781 is distributed throughout the Palaearctic region from Europe to Northeast Asia including the Korean peninsula, but is not found in the Japanese islands (Ministry of Environment ). While a wide‐ranging distribution of G. mopsus was reported across the Korean peninsula in the past, the population size has decreased drastically due to loss or reduction of suitable habitats, changes in animal husbandry methods, and pesticide pollution (Bayartogtokh et al ; Ministry of Environment ). The species has not been found in South Korea since the 1970s, and thus G. mopsus is currently regarded as locally extinct in the country (Ministry of Environment ).…”
Section: Introductionmentioning
confidence: 99%